Pain following blood donation: a questionnaire study of long‐term morbidity (LTM) in blood donors. Issue 1 (31st March 2015) - Sørensen, B. S.; Jørgensen, J.; Jensen, T. S.; Finnerup, N. B.
<x xml:space="preserve">Abstract</x> Background Nerve injury is a main cause of long‐term morbidity following blood donation, but little is known about symptoms, impact, prognosis and underlying cause. Materials and Methods A questionnaire, designed to characterize pain and estimate the prevalence of neuropathic pain, was sent to all blood donors registered with a complication related to 3 297 674 blood donations in Denmark from 2000–2009, with a local complication mainly characterized by pain, with severity grade 'long‐term morbidity' and imputability grade 'definite' or 'probably'. Results The questionnaire was sent to 152 donors (4·6 per 100 000 donations). Response rate was 88/152 (57·9%). At the time of the questionnaire, which was between 12 months and 10 years after the blood donation, 69/88, who responded (78·4%) still experienced symptoms. Of the 69 donors with persistent symptom, pain occurred in 51 donors (74%) was moderate to severe in 24/69 donors (35%) and had an impact on daily activity in 17/69 (25%). Neuropathic pain was estimated to be the underlying cause of symptom in 30–52% of the 69 donors with persistent symptoms, using three different systems for estimation, corresponding to 0·6–1·1/100 000 donations. Discussion Although a rare complication, nerve injury after blood donation may lead to long‐term morbidity and may become chronic in a small proportion of donors. The most common symptoms are pain, and we estimate that neuropathic pain can be the underlying cause.